2023
DOI: 10.3390/ijms24010882
|View full text |Cite
|
Sign up to set email alerts
|

PLA2G7/PAF-AH as Potential Negative Regulator of the Wnt Signaling Pathway Mediates Protective Effects in BRCA1 Mutant Breast Cancer

Abstract: Past studies have confirmed that aberrant activation of the Wnt/β-catenin signaling is associated with tumorigenesis and metastasis in breast cancer, while the role of platelet-activating factor acetylhydrolase (PLA2G7/PAF-AH) in this signaling pathway remains unclear. In this study, we analyze the functional impact of PAF-AH on BRCA1 mutant breast cancer and explore its relationship to the Wnt signaling pathway. By performing immunohistochemistry, PAF-AH expression and β-catenin expression were examined in bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 58 publications
(60 reference statements)
0
2
0
Order By: Relevance
“…The significance of PLA2G7 in specific cancer types has only been partially studied to date. For example, recent literature revealed that the downregulation of PLA2G7 in a breast cancer cell line (HCC1937) promoted proliferation and migration, suggesting a vital role for PLA2G7 in cancer [ 41 ]. Additionally, PLA2G7 has been implicated in the inflammatory process and associated with tumor immunity.…”
Section: Discussionmentioning
confidence: 99%
“…The significance of PLA2G7 in specific cancer types has only been partially studied to date. For example, recent literature revealed that the downregulation of PLA2G7 in a breast cancer cell line (HCC1937) promoted proliferation and migration, suggesting a vital role for PLA2G7 in cancer [ 41 ]. Additionally, PLA2G7 has been implicated in the inflammatory process and associated with tumor immunity.…”
Section: Discussionmentioning
confidence: 99%
“…Depletion of PLA2G7 reduced intestinal polyposis and tumorigenesis in APC (Min/+) mice [ 66 ]. PLAG7 exhibited protective function in breast cancer via negative regulation of the Wnt signaling pathway [ 67 ]. On the other hand, Liao et al discovered that high PLA2G7 protein level was associated with significantly longer OS than low protein level of PLA2G7 in ovarian cancer patients.…”
Section: Discussionmentioning
confidence: 99%